Early MRD response as a prognostic factor in adult patients with acute lymphoblastic leukemia - Šálek, Cyril; Folber, František; Froňková, Eva; Procházka, Bohumír; Marinov, Iuri; Cetkovský, Petr; Mayer, Jiří; Doubek, Michael (European journal of haematology, 2016)
OBJECTIVE: To evaluate the prognostic power of minimal residual disease (MRD) monitored by polymerase chain reaction at defined time points during early treatment in adult patients with acute lymphoblastic leukemia (ALL). METHODS: Seventy-one patients were treated according to the GMALL 07/2003 protocol and evaluated for MRD in bone marrow by specific clonal rearrangements of Ig/TCR in BCR-ABL negative ALL or fusion gene transcript in BCR-ABL positive ALL. RESULTS: Three-year overall survival (OS) was 94% in patients with BCR-ABL negative ALL reaching complete molecular response (CMR) after the first course of chemotherapy (vs. 32% if MRD >10(-4) ; P = 0.001). Patients with CMR prior to the start of consolidation chemotherapy at week 11 had 3-yr OS 82% (vs. 18% if MRD >10(-4) ; P = 0.001). Patients with BCR-ABL positive ALL showed slower MRD dynamics. There was a trend to better OS in patients with ≥ 4 log reduction of BCR-ABL transcript prior to HSCT (92% vs. 50%; P = 0.065). None of the patients with detectable MRD (both BCR-ABL positive and negative) after HSCT survived 3 yr. CONCLUSION: Early MRD kinetics is an important tool for new prognostication models with direct clinical impact irrespective of standard prognostic factors in patients with BCR-ABL negative ALL.
Keywords: genová přestavba; Aged; Adolescent; Treatment Outcome; bcr-abl fúzní proteiny; Remission Induction; lidé středního věku; imunoglobuliny; senioři; prognóza; lidé; Adult; Antineoplastic Combined Chemotherapy Protocols; Gene Rearrangement; Middle Aged; dospělí; Prognosis; Fusion Proteins, bcr-abl; Female; výsledek terapie; Genes, T-Cell Receptor; Neoplasm, Residual; Male; protokoly protinádorové kombinované chemoterapie; ženské pohlaví; Survival Analysis; mladý dospělý; Humans; mužské pohlaví; Young Adult; analýza přežití; Immunoglobulins; indukce remise; akutní lymfatická leukemie; reziduální nádor; geny TcR; Precursor Cell Lymphoblastic Leukemia-Lymphoma; mladiství